Microbiological Evaluation of Novel Bis-Quaternary Ammonium Compounds: Clinical Strains, Biofilms, and Resistance Study - Nikita Frolov; Elena Detusheva; Nadezhda Fursova; Irina Ostashevskaya; Anatoly Vereshchagin (MDPI AG, 2022)
This work is devoted to the investigation of biocidal properties of quaternary ammonium compounds (QACs) based on pyridine structures with aromatic spacers, and their widely known analogs, against clinically significant microorganisms. This study is focused on investigating their antimicrobial activity (minimum inhibitory concentrations (MICs) and minimum bactericidal concentrations (MBCs)), antibiofilm properties (minimum biofilm inhibitory concentrations (MBICs) and minimum biofilm eradication concentrations (MBECs)), synergetic effect with different alcohols in antiseptic formulations, and bacterial resistance development. It was shown that all combined analogue preparations had a higher level of antibacterial activity against the tested bacterial strains, with a 16- to 32-fold reduction in MICs and MBCs compared to previously used antiseptic preparations. Moreover, hit-QACs demonstrated a stable effect against Gram-negative E. coli, K. pneumoniae, and A. baumannii within a month of incubation. Overall results indicated a high level of antibacterial activity of pyridine-based QACs.